2020
DOI: 10.1039/d0ta02079f
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic and energy storage bifunctional Gd-doped WO3/Ag/WO3films

Abstract: Transparent conductive WGd–Ag–WGd films with superior electrochromic and energy storage performance have been obtained on glass substrates by reactive sputtering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 117 publications
1
11
0
Order By: Relevance
“…The main Na 1s peak at ∼1072.3 eV was associated with the bulk sample, while the second peak at 1071.3 eV might have been connected with Na 2 CO 3 . These peaks all matched well with those of previous reports. , Moreover, based on fitting results from XPS Peakfit software, all fitted peaks moved slightly toward higher binding energy, which indicated that Yb 3+ occupied A sites in KNN . For an ionic compensation mechanism of A site donors in KNN, the presence of A-position vacancies increased conductivity and made it difficult to generate oxygen vacancies in KNN. , The XPS peak movement also illustrated the successful incorporation of Yb 3+ ions.…”
Section: Results and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The main Na 1s peak at ∼1072.3 eV was associated with the bulk sample, while the second peak at 1071.3 eV might have been connected with Na 2 CO 3 . These peaks all matched well with those of previous reports. , Moreover, based on fitting results from XPS Peakfit software, all fitted peaks moved slightly toward higher binding energy, which indicated that Yb 3+ occupied A sites in KNN . For an ionic compensation mechanism of A site donors in KNN, the presence of A-position vacancies increased conductivity and made it difficult to generate oxygen vacancies in KNN. , The XPS peak movement also illustrated the successful incorporation of Yb 3+ ions.…”
Section: Results and Discussionsupporting
confidence: 87%
“…33,38 Moreover, based on fitting results from XPS Peakfit software, all fitted peaks moved slightly toward higher binding energy, which indicated that Yb 3+ occupied A sites in KNN. 39 For an ionic compensation mechanism of A site donors in KNN, the presence of A-position vacancies Yb A •• increased conductivity and made it difficult to generate oxygen vacancies in KNN. 4,40 The XPS peak movement also illustrated the successful incorporation of Yb 3+ ions.…”
mentioning
confidence: 99%
“…Starting with the fundamental electrochemical reaction, electrochromic performances of the WO 3− x depend on the transport rate of the cations and electrons as well as the ability to accommodate the cations in the film. Different advanced strategies have been studied to improve electrochromic performances such as the combination of crystalline and amorphous WO 3− x [ 20 , 21 ], regulation of nanotopography [ 6 , 22 , 23 ], element doping [ 18 , 24 , 25 ], and construction of composite materials [ 26 , 27 ]. On the one hand, the structure construction of tungsten oxide almost concentrates on the transport behavior of cations.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochromic tungsten oxide film transforms from a colorless film in the bleached state to a dark blue film in the colored state under the application of a potential. This transformation corresponds to the electronic transition between the different valence states of the tungsten ion, namely W +5 and W +6 , obtained by the redox reaction described by, 23,24 ()transparent0.25emWO3+xLi++xeLixWO30.25em()deep blue …”
Section: Introductionmentioning
confidence: 99%